2022
DOI: 10.1097/pg9.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

The Resolution of Severe Iron-Deficiency Anemia After Successful Eradication of Helicobacter pylori in Teenagers

Abstract: Objectives: Long-term follow-up studies with Helicobacter pylori eradication therapy in children with H. pylori -associated iron-deficiency anemia (IDA) are scarce. We investigated whether successful H. pylori eradication would result in maintaining resolution of recurrent and/or refractory IDA in a cohort of teenagers in Japan. Methods: In this case series, 7 H. pylori -infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The level of anemia in gastritis is not dependent on the presence of Helicobacter [14]. However, in a study by S. Kato et al, it was shown that hemoglobin, serum iron, and ferritin values significantly increased 2-3 months after eradication therapy [15,16].…”
Section: Types Of Gastritis and Clinical Manifestationsmentioning
confidence: 94%
“…The level of anemia in gastritis is not dependent on the presence of Helicobacter [14]. However, in a study by S. Kato et al, it was shown that hemoglobin, serum iron, and ferritin values significantly increased 2-3 months after eradication therapy [15,16].…”
Section: Types Of Gastritis and Clinical Manifestationsmentioning
confidence: 94%
“…Eradication of H. pylori results in reversal of long-standing IDA [28,29]. Furthermore, successful eradication of H. pylori leads to long-term resolution of refractory or recurrent IDA in Japanese teenagers [27]. Taking together the cumulative evidence described above, it is concluded that H. pylori causality on childhood IDA has been established.…”
Section: Clinical Evidencementioning
confidence: 94%
“…In one study of twins with H. pylori infection [89], it was suggested that host genetic factors are important in the development of ID or IDA. In a recent study [27], one sibling case with recurrent H. pyloriassociated IDA showed long-term resolution after successful eradication therapy.…”
Section: Host Genetic Factorsmentioning
confidence: 95%
See 2 more Smart Citations